PERAN BRAND AWARENESS MEMEDIASI PENGARUH SOCIAL MEDIA MARKETING TERHADAP PURCHASE INTENTION PRODUK KOSMETIK SCARLETT WHITENING (STUDI PADA MASYARAKAT DI KOTA DENPASAR) - Primawardani, Ni Made Eny; Rahanatha, Gede Bayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.10.TAHUN.2023, 2023)
Purchase intention is a stage for potential consumers to act before making a purchase decision. This study aims to examine the role of mediating brand awareness in the influence of social media marketing on the purchase intention of Scarlett Whitening cosmetic products among people in Denpasar City. The population in this study is the people in the city of Denpasar who have never purchased Scarlett Whitening products. The sample was determined using a purposive sampling by distributing questionnaires to 110 respondents. The analysis technique used is descriptive statistical analysis, path analysis, Sobel test and VAF test. The results of the study show that social media marketing has a positive and significant effect on purchase intention. Social media marketing has a positive and significant effect on brand awareness. Brand awareness has a positive and significant effect on purchase intention. Brand awareness can mediate the effect of social media marketing on purchase intention. The results of this study have an impact on marketing strategies, especially for Scarlett Whitening's management to pay more attention to social media marketing and brand awareness in order to increase purchase intention.